Emergency cesarean section in case of aneurysm of the muscular intraventricular septum with neonatal follow-up - a case report and review of the literature - Płużańska, Joanna; Więcek, Jacek; Krekora, Michał; Kiełbasicz-Binikowska, Jolanta; Talar, Tomasz; Słodki, Maciej; Respondek-Liberska, Maria (Prenatal Cardiology, 2016)
We present the case of aneurysm of the muscular intraventricular septum with accompanying cardiomegaly and abnormal venous flow patterns requiring emergency cesarean section and specialized neonatal treatment. At the age of 8 months our patient has no clinical symptoms with a 6 mm scar in intraventricular muscular septum.